Enhancement of growth performance in pre-weaning suckling Boer kids supplemented with creep feed containing alfalfa - Nay Naing Htoo; Aung Tun Khaing; Yusuf Abba; Nwe Nwe Htin; Jesse Faaz Firdaus Abdullah; Than Kyaw; Mohd Azam Khan Goriman Khan; Mohd Azmi Mohd Lila (2015)
This study examined the effects of creep feed (CF) supplementation (with or without Alfalfa) on the pre-weaning growth performance of nursing goat kids.